Enrichment of ultraconserved elements among genomic imbalances causing mental delay and congenital anomalies - Mayo Sonia; Quiroga Ramiro; Blesa David; Oltra Silvestre; Roselló Mónica; Monfort Sandra; Martínez Francisco; Orellana Carmen (BMC, 2010)
Abstract Background The ultraconserved elements (UCEs) are defined as stretches of at least 200 base pairs of human DNA that match identically with corresponding regions in the mouse and rat genomes, albeit their real significance remains an intriguing issue. These elements are most often located either overlapping exons in genes involved in RNA processing or in introns or nearby genes involved in the regulation of transcription and development. Interestingly, human UCEs have been reported to be strongly depleted among segmental duplications and benign copy number variants (CNVs). However no comprehensive survey of a putative enrichment of these elements among pathogenic dose variants has yet been reported. Results A survey for UCEs was performed among the 26 cryptic genomic rearrangements detected in our series of 200 patients with idiopathic neurodevelopmental disorders associated to congenital anomalies. A total of 29 elements, out of the 481 described UCEs, were contained in 13 of the 26 pathogenic gains or losses detected in our series, what represents a highly significant enrichment of ultraconserved elements. In addition, here we show that these elements are preferentially found in pathogenic deletions (enrichment ratio 3.6 vs. 0.5 in duplications), and that this association is not related with a higher content of genes. In contrast, pathogenic CNVs lacking UCEs showed almost a threefold higher content in genes. Conclusions We propose that these elements may be interpreted as hallmarks for dose-sensitive genes, particularly for those genes whose gain or loss may be directly implied in neurodevelopmental disorders. Therefore, their presence in genomic imbalances of unknown effect might be suggestive of a clinically relevant condition.